Chronic periodontitis is associated with lacunar infarct: a case–control study. (15th July 2016) - Leira, Y.; López‐Dequidt, I.; Arias, S.; Rodríguez‐Yáñez, M.; Leira, R.; Sobrino, T.; Campos, F.; Blanco, M.; Blanco, J.; Castillo, J.
Abstract : Background and purpose: Chronic periodontitis (ChP) and lacunar infarct (LI) are two common diseases amongst the elderly. Although several studies have shown an association between ischaemic stroke and ChP, little is known about the relationship between ChP and LI. The study aims to investigate whether ChP is associated with the presence of lacunar stroke. Methods: An age‐ and gender‐matched case–control study of 62 cases (subjects diagnosed with LI) and 60 controls is reported. Clinical periodontal measures (probing pocket depth, recession, clinical attachment level, full mouth plaque score and full mouth gingival bleeding on probing score) were assessed, and associated risk factors for periodontitis and lacunar stroke were ascertained by means of a structured questionnaire. Results: Chronic periodontitis showed a strong association with LI after adjusting for common vascular risk factors (odds ratio 4.20; 95% confidence interval 1.81–10.20; P = 0.001). Likewise, severe ChP and LI also tended to be significantly associated, independent of other vascular covariates (odds ratio 3.53; 95% confidence interval 1.07–12.77; P = 0.04). Conclusions: Chronic periodontitis was independently associated with the presence of LI after adjusting for well‐known vascular risk factors for lacunar stroke. Further observational studies are necessary to investigate the pathophysiological mechanisms that can explain this relationship.